O17 Profile of intracranial artery calcifications and effect on endovascular stroke treatment. (29th August 2022) - Rodrigo-Gisbert, M; Requena, M; Rubiera, M; Lozano, P; De Dios Lascuevas, M; García-Tornel, Á; Olivé-Gadea, M; Boned, S; Muchada, M; Rodríguez-Villatoro, N; Rodríguez-Luna, D; Juega, JM; et al.
Abstract : Background: Acute ischemic stroke with large or medium-vessel occlusion associated to intracranial artery calcification (IAC) is an infrequent entity presumably associated with intracranial atherosclerotic disease. We aimed to assess IAC profile and its effect on endovascular treatment procedural results and clinical outcomes. Methods: We retrospectively evaluated all consecutive patients treated with thrombectomy from January-2020 to March-2021 in our institution. We described IAC imaging findings (length, density and location pattern) on baseline non-contrast computed tomography. We also analyzed the association between IAC profile and procedural/clinical outcomes using adjusted logistic regression models. Results: From 320 patients, 17 presented a symptomatic-IAC (s-IAC: 5, 3%), 63 an asymptomatic-IAC (a-IAC: 19, 7%) and in 240 no IAC was observed (no-IAC: 75%). Symptomatic-IAC were more frequently found in terminal internal carotid (6/17: 35, 2%) and basilar arteries (3/17: 17, 6%), those patients usually presented asymptomatic IAC in 52, 1%. The rate of no recanalization (mTICI 0–2a) before stent placement was higher in s-IAC (64.7%) than in a-IAC (15.9%; p<0, 001 ) or non-IAC (13.7%; p<0, 001 ). Intracranial angioplasty/stenting was more frequently performed in s-IAC (23.5%) than in a-IAC (1, 6%; p=0, 006 ) or non-IAC (4, 2%; p=0, 009 ). After adjusting for identifiable confounders, symptomatic-IAC was an independent predictor of no recanalization (OR 10, 36, 95%CI 2, 96–36, 25; p<0, 001 ), intracranial angioplasty/stenting (OR 11, 35; 95%CI 1, 72–75, 02 ; p=0, 012 ) and poor functional outcome (90-day mRS ≥ 3 OR 5, 04; 95%CI 1, 03–24, 52; p=0, 045 ). Conclusions: Intracranial arterial calcifications within the symptomatic vessel are associated with worse angiographic and functional outcomes. Identification of symptomatic-IAC on baseline imaging may predict need of intracranial stenting and determine their optimal endovascular treatment strategy. References: Maurer CJ, et al . Endovascular Thrombectomy of Calcified Emboli in Acute Ischemic Stroke: A Multicenter Study. AJNR . 2020 Mar;41 (3):464–468. Johnson S, Mccarthy R, Fahy B, et al . Development of an in vitro Model of Calcified Cerebral Emboli in Acute Ischemic Stroke for Mechanical Thrombectomy Evaluation. J Neurointerv Surg . 2020 Oct;12 (10):1002–1007. Dobrocky T, et al . Thrombectomy of Calcified Emboli in Stroke. Does Histology of Thrombi Influence the Effectiveness of Thrombectomy? J Neurointerv Surg . 2018 Apr;10 (4):345–350. Raghib MF, et al . Acute Treatment of Stroke due to Spontaneous Calcified Cerebral Emboli Causing Large Vessel Occlusion. J Clin Neurosci . 2018.Jan;47:56–61. Do you have any conflict of interest to declare? : No